A High‐Rate and Stable Quasi‐Solid‐State Zinc‐Ion Battery with Novel 2D Layered Zinc Orthovanadate Array. Issue 32 (2nd July 2018) - Chao, Dongliang; Zhu, Changrong (Rose); Song, Ming; Liang, Pei; Zhang, Xiao; Tiep, Nguyen Huy; Zhao, Haofei; Wang, John; Wang, Rongming; Zhang, Hua; Fan, Hong Jin
Abstract: Zinc‐ion batteries are under current research focus because of their uniqueness in low cost and high safety. However, it is still desirable to improve the rate performance by improving the Zn 2+ (de)intercalation kinetics and long‐cycle stability by eliminating the dendrite formation problem. Herein, the first paradigm of a high‐rate and ultrastable flexible quasi‐solid‐state zinc‐ion battery is constructed from a novel 2D ultrathin layered zinc orthovanadate array cathode, a Zn array anode supported by a conductive porous graphene foam, and a gel electrolyte. The nanoarray structure for both electrodes assures the high rate capability and alleviates the dendrite growth. The flexible Zn‐ion battery has a depth of discharge of ≈100% for the cathode and 66% for the anode, and delivers an impressive high‐rate of 50 C (discharge in 60 s), long‐term durability of 2000 cycles at 20 C, and unprecedented energy density ≈115 Wh kg −1, together with a peak power density ≈5.1 kW kg −1 (calculation includes masses of cathode, anode, and current collectors). First principles calculations and quantitative kinetics analysis show that the high‐rate and stable properties are correlated with the 2D fast ion‐migration pathways and the introduced intercalation pseudocapacitance. Abstract : New electrodes of Zn‐ion batteries . Strategies of novel layered mesoporous zinc orthovanadate, a Zn nanoarray, and a solid‐state electrolyte (SSE) are used to alleviate the dendrite growth problem. Intercalation pseudocapacitance in the cathode improves the rate capability. High energy and power densities are achieved with a depth of discharge of 100% for the cathode and 66% for the zinc anode.